2003
DOI: 10.1128/iai.71.2.857-863.2003
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Chickens againstEscherichia coliInfections by DNA Containing CpG Motifs

Abstract: Synthetic oligodeoxynucleotides (ODN) containing CpG motifs (CpG-ODN) have been shown to be effective immunoprotective agents in murine models for a variety of viral, intracellular bacterial, and protozoan infections. Until now, the use of CpG-ODN to protect against extracellular bacterial infections has not been reported. The objective of this study was to investigate the effect of CpG-ODN against cellulitis and colibacillosis in broiler chickens, using a well-established model. At 22 days of age, birds recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(83 citation statements)
references
References 29 publications
4
79
0
Order By: Relevance
“…Encouraging results have been obtained in poultry production with the DNA-containing preparation CpG-ODN ® , and with a patented version of Aloe vera aqueous extract (Gomis, et al, 2003;Durrani, et al 2008). Another potentially useful immune-stimulating pharmaceutical preparation based on glycyrrhizic acid (GRA) has been used in human medicine.…”
Section: Introductionmentioning
confidence: 99%
“…Encouraging results have been obtained in poultry production with the DNA-containing preparation CpG-ODN ® , and with a patented version of Aloe vera aqueous extract (Gomis, et al, 2003;Durrani, et al 2008). Another potentially useful immune-stimulating pharmaceutical preparation based on glycyrrhizic acid (GRA) has been used in human medicine.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic class B CpG ODN 2007 and non ODN (Gomis et al 2003) were purchased from TIB Molbil, Synntheselabor mbH (Berlin, Germany), both possessing a phosphorothioate backbone. All the ligands used were re-suspended in sterile phosphate buffered saline (PBS pH 7.4).…”
Section: Tlr Ligandsmentioning
confidence: 99%
“…CpG ODNs are utilized for a variety of therapeutic purCorrespondence to: K. Chrząstek, e-mail: klaudia.chrzastek@up.wroc.pl, tel./fax: 0048 71 532 03 36 poses. Gomis et al (2003Gomis et al ( , 2004 demonstrated that prophylactic treatment of chickens with class B CpG ODN enhanced host immunity to numerous pathogens such as Escherichia coli. A number of reports regarding the effects of ODNs on chicken cells cultured in vitro (He et al 2003, 2006, Schwarz et al 2007 or as a vaccine adjuvant (Linghua et al 2007, Zhang et al 2008 have been published.…”
Section: Introductionmentioning
confidence: 99%
“…IL-10 was likely derived from macrophages and monocytes, but not from plasmacytoid dendritic cells or T cells on the basis of the immunohistochemistry results. Local inflammatory reactions induced by CpG injections have been reported in several studies including in human skin [24,25,26]. The presence of localized cell recruitment is reported to be necessary for the immunoprotective effects of CpG against viral and bacterial infection since they are activated to produce IFN-α and IFN-γ [24, 25].…”
Section: Discussionmentioning
confidence: 99%